Design diary of Alex Choi : a record of a decade's design - Ng, Michelle (Hong Komg : Pace Publishing, 2010)
Being a Hong Kong interior designer -- Retail -- Office -- Hospitality -- Residential -- Miscellaneous -- Ping Pong dialogue -- Words of thanks.